Management of erosive oral lichen planus - Naritasari, Fimma; Argadianti, Ayu Fresno; Fadilah, Nida Arum (MKGK (Majalah Kedokteran Gigi Klinik) (Clinical Dental Journal) UGM, 2024)
Oral lichen planus (OLP) is an autoimmune disease that commonly affects the mucocutaneous area. The etiology of OLP remains unclear, but several factors are considered risk factors, such as chronic liver disease (hepatitis C infection), stress, genetics, hypertension, diabetes, smoking, and tobacco chewing. OLP often causes pain, especially during exacerbation periods. OLP management aims to reduce symptoms, improve clinical conditions, reduce the riskof oral cancer, and maintain oral health. This case report presents a case of OLP in a 54-year-old Javanese female patient with complaints of pain in her oral cavity that persisted for three weeks. The same condition occurred three months earlier, but it resolved without treatment. Clinical examination of pathognomonic features of OLP in the form of white, mesh-shaped lesions (Wickham striae) on the buccal and gingival mucosa is the basis for determining thediagnosis of OLP. The ulcerative type of OLP is established based on the appearance of ulcerated lesions in the tongue area and complaints of pain. The patient had a history of hypertension with regular consumption of captopril for the past three years., but there was no documented history of allergies. The results of the psychological assessment with DASS-42 revealed that the patient experienced very severe anxiety, moderate depression, and mild stress. Management in this case was done by prescribing topical corticosteroid, which is dexamethasone mouthwash, whichwas gargled by the patient twice a day. One month after therapy, the ulcerative lesions on the tongue resolved entirely, and pain complaints disappeared. In this case, topical corticosteroids effectively reduced symptoms and improved the clinical condition. However, long-term follow-ups are necessary to ensure that the lesion does not transform into a malignant lesion.